2011
DOI: 10.1111/j.1600-0838.2010.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Resting and post‐exercise serum biomarkers of cardiac and skeletal muscle damage in adolescent runners

Abstract: This study examined the response of serum biomarkers of cardiac and skeletal muscle damage at rest and after a routine workout of 21 km run in 12 male adolescent (16.2±0.6 years) long-distance runners. Biomarkers of cardiac [troponins (cTnT, cTnI), creatine kinase MB mass (CK-Mbmass)] and skeletal muscle [creatine kinase (CK), lactate dehydrogenase (LDH), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and hydroxybutyrate dehydrogenase (HBD)] damage were assayed at rest, 2, 4 and 24 h post-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
65
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 15 publications
10
65
1
1
Order By: Relevance
“…Some caution should be expressed in this comment based on the small, but statistically significant, differences in CV work undertaken during exercise in PBA when compared to JBA as well as that if you compare JBA to ABA (still a biological age comparison with similar weekly training volumes) then a difference is noted with JBA exhibiting a larger response than older ABA. This comparison compares more favorably to past work assessing the impact of biological age on post-exercise cTn appearance [18,19,24,25]. The complex interaction here of biological age, training volume and elite athlete status is complex to "un-pick" and requires further work.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Some caution should be expressed in this comment based on the small, but statistically significant, differences in CV work undertaken during exercise in PBA when compared to JBA as well as that if you compare JBA to ABA (still a biological age comparison with similar weekly training volumes) then a difference is noted with JBA exhibiting a larger response than older ABA. This comparison compares more favorably to past work assessing the impact of biological age on post-exercise cTn appearance [18,19,24,25]. The complex interaction here of biological age, training volume and elite athlete status is complex to "un-pick" and requires further work.…”
Section: Discussionmentioning
confidence: 62%
“…Nevertheless, the influence of training level on cTn release has not yet been evaluated in a controlled study with disparate groups in terms of training or athletic status. Evidence to date also suggests increased cTn appearance after exercise in adolescent athletes, possibly due to their immature cardiac muscle [9,18,19,24,25], although only Tian et al [9] directly compared adult and adolescent athletes in a controlled study. Currently, it is unknown if the cTn response to intermittent exercise is similar in adults and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports on animals (Chen et al 2000) and humans (Nie et al 2008;Scharhag et al 2008;Shave et al 2007) have observed elevated serum cTnT/cTnI after prolonged exercises that can exceed clinical cut-off value for acute myocardial infarction (Nie et al 2010;Shave et al 2007). The appearance of cTnT/cTnI in apparently healthy, young people participating in prolonged exercise has raised concerns about the cardiovascular health consequences of such exercise (La Gerche and Prior 2007), and this predicates the need to determine why and how these elevations occur.…”
Section: Introductionmentioning
confidence: 99%
“…Nieoet al 13 mentioning that significant increases in concentrations of CK and LDH after training suggest accumulation of fatigue caused by daily exercise and physical unsuitability to it, confirming the risk of muscle injury.…”
Section: Discussionmentioning
confidence: 99%